2008
DOI: 10.1182/blood-2007-12-130609
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of MHC class II expression in tumor-associated macrophages by decoy receptor 3

Abstract: Decoy receptor 3 (DcR3) is a member of the TNF receptor superfamily and is up-regulated in tumors originating from a diversity of lineages. DcR3 is capable of promoting angiogenesis, inducing dendritic cell apoptosis, and modulating macrophage differentiation. Since tumor-associated macrophages (TAMs) are the major infiltrating leukocytes in most malignant tumors, we used microarray technology to investigate whether DcR3 contributes to the development of TAMs. Among the DcR3-modulated genes expressed by TAMs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 53 publications
5
110
0
Order By: Relevance
“…We previously found that DcR3 modulates macrophage differentiation and activation, as well as suppresses MHC-II expression in TAMs via epigenetic regulation in vitro (33,34). The current study investigated whether DcR3 promotes tumor growth via the modulation of TAMs in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that DcR3 modulates macrophage differentiation and activation, as well as suppresses MHC-II expression in TAMs via epigenetic regulation in vitro (33,34). The current study investigated whether DcR3 promotes tumor growth via the modulation of TAMs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…DcR3-treated macrophages display attenuated phagocytic activity, with downregulated CD14 and CD16, as well as impaired production of proinflammatory cytokines in response to LPS (33). Recently, we further demonstrated that DcR3 downregulates MHC-II expression in macrophages via epigenetic control, and histone deacetylase (HDAC) inhibitor restores MHC-II expression by reversing DcR3-mediated deacetylation of the promoter of transcription factor CIITA (34). However, whether DcR3 promotes tumor growth and progression via the induction of TAMs in vivo remains to be elucidated.…”
mentioning
confidence: 97%
“…Elevated serum concentrations of DcR3 have been detected in patients with various malignant cancers, e.g., cancers of the esophagus, stomach, glioma, lung, colon, rectum, and pancreas (1,4,16,18,19). In tumorigenesis, DcR3 not only helps tumor cells to escape immune surveillance by neutralizing FasL-or lymphotoxin-like, exhibits inducible expression, and competes with HSV glycoprotein D for HVEM, a receptor expressed by T lymphocyte-mediated cell death (1,2), down-regulating MHC-II expression by tumor-associated macrophages (20), and inducing immune suppression, as described above, but also contributes to the development of a microenvironment suitable for tumor growth, e.g., by inducing angiogenesis (21). DcR3 is therefore a critical factor in tumor progression.…”
Section: Ecoy Receptor 3 (Dcr3)mentioning
confidence: 99%
“…Using microarray, Chang et al revealed that genes characteristically expressed by tumor-associated macrophages were upregulated by DcR3 (30). In the current study, we first demonstrated the expression profiles of genes in RA-FLS regulated by DcR3.…”
Section: Discussionmentioning
confidence: 92%